Uncertainty and challenges in contemporary economic behaviour - Özen, Ercan; Grima, Simon (Emerald Publishing Limited, 2020)
Every day presents new challenges as the face of global economics changes. In this first book in the Emerald Studies in Finance, Insurance, and Risk Management, expert editors and contributors come together to discuss global response to new uncertainty and challenges.- Resumé vydavatel
Includes index.
Keywords: hospodářské dějiny -- 21. století; ekonomické chování -- 21. století; economic history -- 21st century; economic behavior -- 21st century; elektronické knihy; sborníky; electronic books; papers of several authors